Science literacy in the age of disinformation: Building bridges to address the complexity of the challenge. - Dos Santos Silva, Erasmo Moises; Arroio, Agnaldo (Corporación Universitaria Minuto de Dios - UNIMINUTO, 2023)
Science education and media and information literacy (MIL) significantly contribute to the current landscape of contested knowledge surrounding science and scientists, as evidenced by movements against COVID-19 health protocols. Nonetheless, a broader view than that typically portrayed of complexity is required. This chapter aims to offer recommendations to avoid counter-productive approaches based on problematic assumptions, such as considering all types of untrustworthy information as fake news. Thus, this chapter aims to problematize views about the information disorder phenomenon in the context of natural science in Brazil by providing a complex and coherent vision of the issue in the context of natural science educators and education.
Capítulo completo en acceso abierto que hace parte de la obra Media and information literacy for the public good: UNESCO MILID Yearbook 2023.
Keywords: Educación científica; Trastorno de la información; Educación; Prácticas docentes; Science education; Information disorders; Rake news; STEAM education; Teaching practices; Literacy (Education) — Case Studies; Primary Education 3.Adult Literacy — Research; Education and Development; Vocational Training; Media Literacy